E-014 The "sandwich" technique for interventional management of AIS. (12th July 2011) - Crudup, J; Hartley, B; Baxter, B
Abstract : Introduction: Devices currently used in the endovascular treatment of acute ischemic stroke employ either aspiration or mechanical thrombectomy separately but not in combination. Recent advancements in catheter design have made the delivery of coaxial catheters to the intracranial occlusive lesion standard practice. At our institution, we have found the use of Concentrics Distal Access Catheter (DAC) adjunctively with a thrombectomy device to be effective in increasing catheter stability and enhancing clot retrieval. Further, we have found a novel use of the DAC during mechanical thrombectomy. With the DAC tip being placed at or within the proximal end of the clot and the retriever embedded distally in the clot, we employ aspiration through the DAC during the retrieval process. The clot is "sandwiched" between the combined forces of aspiration and mechanical extraction. DAC carries an approval for aspiration in Europe and Canada, but in the USA this is an off label use of the catheter. The aim of this "sandwich" technique is to enhance the thrombectomy procedure by decreasing the number of passes required and shortening the time to revascularization. Methods: A retrospective review of mechanical thrombectomy cases performed at our institution after introduction of the DAC was conducted. Cases were reviewed from November 24, 2008 to April 1, 2011. From these cases, 25 were found in which the "sandwich" technique was utilized. The imaging and procedural reports were reviewed to insure that an appropriate and consistent "sandwich" technique was performed. Outcome measures analyzed were the rate of successful revascularization (using the TICI scoring system), 90-day Modified Rankin Scale (mRS) score, and the 90-day mortality rate. Results: 25 patients were identified (mean age, 65 years; gender, males 48%, females 52%; mean baseline NIHSS, 18). Successful revascularization (defined as achieving a TICI score of 2a, 2b or 3) was achieved in 20/25 (80%) patients. The rate of good outcomes (defined as a 90-day mRS 0–2) was achieved in 11/25 (44%). The 90-day mortality rate was 32% (8/25). Conclusions: The "sandwich" technique yields favorable successful revascularization rates and good clinical outcomes as compared to current endovascular therapies reported in the literature for acute ischemic stroke treatment. Although not initially intended for this purpose, we feel that using the DAC to adjunctively aspirate during the mechanical thrombectomy procedure to be helpful. Further study in a larger patient population to explore whether this technique offers benefit over "traditional" thrombectomy is required.